Comparative study on neuroprotective effects of soybean and tempeh extracts / Aliya Ahmad - Ahmad, Aliya (2013)
Although there were several studies regarding the benefits of soybean to health, only a few focused on neuroprotective effects. Furthermore, the role of fermented soybean has not been documented as neuroprotective agent. The present study is therefore aimed to compare the neuroprotective effects of total isoflavones from soybean and tempeh extracts. Total isoflavones were extracted from soybean and tempeh. The methanolic extracts were subjected to HPLC analysis to quantify the amount of isoflavones present in soybean and tempeh. The animal study was set up for two models as normal and scopolamine-induced (dementia model). The rats (n=6) were given oral administration of soybean and tempeh extracts (10, 20 and 40 mg/kg), piracetam (400 mg/kg) as standard and normal saline as control for 15 days. Both models were tested for radial arm maze task (RAM) and elevated plus maze (EPM) task for the measurement of memory and learning behavior. On 30th day, after the behavior study and treatment, the animals were sacrificed. The brain and serum were collected for superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), glutathione reductase (GR), thiobarbituric acid (TBARS), nitric oxide (NO), acetylcholine (ACh) and acetylcholinesterase (AChE) measurement. For neuroinflammatory analysis, two cytokines (IL-10 and IL-1P) were also measured. The HPLC analysis showed that tempeh possessed higher aglycone level which indicated higher bioavailability as compared to soybean glycoside. The results of the in vitro studies highlighted that tempeh extract exerted more radical scavenging effect and ferrous ion chelating as compared to soybean extract. For p-secretase (BACE1) inhibition, tempeh extract also showed a lower IC50 value as compared to soybean extract although not enough evidence to statistically significant. In vivo memory models, showed significant improvement of memory enhancing by both extracts as compared to control in both normal and scopolamine-induced models. Significant values (p < 0.05) were higher in tempeh treated groups. Similarly, the improvement of antioxidants SOD, CAT, GSH, GR and reduction in oxidative parameters LPO and NO were higher in tempeh compared to control. Furthermore, higher cholinergic activity such as improved the Ach level and declined the AChE activity were observed in tempeh as compared to control. For the inflammatory study, IL-10 was significantly up-regulated while IL-ip was significantly down-regulated in both soybean and tempeh treated group as compared to control and scopolamine group. This suggested soybean and tempeh as a beneficial food for anti-inflammation within the brain. As a conclusion, tempeh extract exerted higher neuroprotective activities than soybean. Hence, consumption of tempeh, is more health beneficial than soybean.